A Comparative Analysis of Islamic and Non-Islamic Banking using Financial Asset-Quality Ratio and Liquidity Ratio - Prastawa, Irvantara; Zen, Tuntun Salamatun (Journal of Business and Management, 2016)
The core objective of this research is to compare and examine financial performance of Islamic banks agains Non-Islamic banks. The research observes that Islamic banking has made unprecedented progress over recent years. In Indonesia specifically, they had been increasing their assets by an average of 43% annually since 2007, and their share of the banking sectorâ€™s total assets is growing fast.Â Focusing on those asset growth, this research aims to compare it to the main banking system used, which is Non-Islamic banks or Conventional banks, by focusing on the asset side of the financial performance. The financial performance measurement were expressed in six financial ratios in which were categorized into Asset-Quality and Liquidity. These six ratios are: Provision to Earning Assets (PEA), Loan Ratio (LR), Loan to Deposits (LTD), Cash to Assets (CTA), Cash to Deposits (CTD), and Return on Asset (ROA). The data was based on balance sheets and income statements of Islamic and Non-Islamic banks from year 2004 to 2014. To test the hypotheses, Mann-Whitney was utilized to compare those financial performances. In general, the research found significant difference in all six ratios, with each bank had their own better performance in some ratios.